TAFSIR VISUAL Kajian Resepsi atas Tafsir dan Ilustrasi dalam Tafsir Juz ‘Amma for Kids - Zahro’, Nafiatuz (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2015)
rchange-newline"> Al-Qur’an as hudan li al-nās and rahmatan li al-‘ālamīn, can not be comprehended the mean without any exegesis. In order that Al-Qur’an and Exegesis are always easy given in the life and proved its existence which shalih li kulli zaman wa makan, they era does not only consider social character change from the space and the time, but the subject too. It is consumer that is containing of various ability standard and age. Unfortunately, almost all exegesis is product that presented as adult consumption; beside in this fact the modernization demand each element of life to begin all aspect from children age for the maturation and the success future. One of the works from several works that has been established to fulfil the children needed is Tafsir Juz ‘Amma for Kids with the new thing that most shown from this work is illustration. In this article, It uses reception method to fid listener reaction and AlQur’an reader in the meaning explanation. Reception that is done by commentator has succeeded to be concretized into exegesis text with simple language; beside the reception that it is done by illustrator has succeeded to be concretized into visual language that is illustration that in the fial accompany in the gotten up of a functional relation between both of them. The existence of exegesis and illustration are cooperation and it is a form of integration-interconnection. Illustration which as functional before has become a helper media, fially it has potential as independent to be an exegesis that is “Visual Exegesis.”